Factors affecting surgical site infection rate after elective gastric cancer surgery - (:unkn) unknown (TURKISH SURGICAL ASSOC, 2016)
Objective: Surgical site infection (SSI) is a common complication after surgery and is an indicator of quality of care. Risk factors for SSI are studied thoroughly for most types of gastrointestinal surgeries and especially colorectal surgeries, but accumulated data is still lacking for gastric surgeries. We studied the parameters affecting SSI rate after gastric cancer surgery. Material and Methods: Consecutive patients, who underwent elective gastric cancer surgery between June and December 2013, were included. Descriptive parameters, laboratory values and past medical histories were recorded prospectively. All patients were followed for 1 month. Recorded parameters were compared between the SSI (+) and SSI (-) groups. Results: Fifty-two patients (mean age: 58.87 +/- 9.25 [31-80]; 67% male) were included. SSI incidence was 19%. ASA score =3 (p<0.001), postoperative weight gain (p<0.001), smoking (p=0.014) and body mass index (BMI) >= 30 (p=0.025) were related with a higher SSI incidence. Also patients in the SSI (+) group had a higher preoperative serum C-reactive protein level (p=0.014). Conclusion: We assume that decreasing BMI to <30, stopping smoking at least 3 weeks before the operation, and preventing postoperative weight gain by avoiding excessive intravenous hydration will all help decrease SSI rate after gastric surgery.
Keywords: Gastric cancer; surgical site infection; risk factors; C-REACTIVE PROTEIN; RISK-FACTORS; CDC DEFINITIONS; OBESITY; GASTRECTOMY; OVERWEIGHT